Sediment Movements in Estuary of Siak River, Riau Basin, Indonesia - Mubarak Mubarak; Ahmad Nurhuda (Faculty of Geography, Universitas Gadjah Mada, 2021)
Siak river has a long history as a transportation lane in the east of Sumatera. From traditional to timber transportations are dependent on this river. Now the river is a severe suffering pollutant spill from many sources. Anthropological activities were higher contributions in the degradation of river environments. Many works were reported about pollution in Siak river. But how the distribution of model sediment transport in the mouth of the river is less to be explained. We consider hydrodynamics model of the mouth of Siak river for modeling the sediment distribution. This simulation gives a fundamental and clear understanding of how total solid sediment (TSS) distribution when flood and ebb tide happens. At ebb tide, TSS dispersion is higher than at flood tide. There is found that the sediment is concentrated in the plume of Siak river in Bengkalis strait. The composition of the sediment is dominated by organic matters.